Some Cases of Flouted Maxims by Some Characters’ Communication Style in Eat Pray Love (Universitas Islam Negeri Sunan Ampel Surabaya, 2013)
The way of communication can affect the rational and cooperative communication. The speaker and the hearer (interlocutors) in talk exchange may disobey the maxims of quantity, quality, manner, and relevant. The result is the cooperative principles flouted in communication. Such as in Eat Pray Love, involves three countries which have different communication style found some flouted maxims. They are; flouted maxims of quantity, quality, manner, and relevant. The communication style affects the way of speaking in each country. For instance, the interlocutors’ response is redundant, unclear, and out of the point in communication.